MENINGKATKAN KEMAMPUAN MENULIS SEDERHANA MELALUI MODEL SNOWBALL THROWING PADA PESERTA DIDIK KELAS II SDN 01 TELAGA BIRU - Rahmatia Saridi; Abd Hamid Isa; Yurni Rahman (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The purpose of this study was to improve simple writing skills through the snowball throwing model in second-grade students of SDN 01 Telaga Biru. The type of research used in this study was classroom action research with 30 second-grade students as subjects. This study used techniques such as interviews, observation, tests, and documentation. Data analysis techniques included teacher activities, student activities, and simple writing skills. The research was conducted in two cycles: Cycle I with three meetings and Cycle II with two meetings, with four stages: planning, implementation, observation, and reflection. The initial observation revealed that only 6 students, or 20%, met the ability criteria, and 24 students, or 80%, did not meet the ability criteria. Furthermore, in Cycle I, there was an increase, with 18 students, or 60%, meeting the ability criteria. In Cycle II, 27 students, or 90%, met the ability criteria. The results achieved in Cycle II exceeded the success indicator. Therefore, it can be concluded that the snowball throwing model can improve the simple writing skills of second-grade students at SDN 01 Telaga Biru.